2005
DOI: 10.1111/j.1468-2362.2005.00160.x
|View full text |Cite
|
Sign up to set email alerts
|

Macroeconomic Fundamentals and Net Portfolio Investment Between Developed Regions*

Abstract: Our paper investigates how macroeconomic fundamentals correlate with net capital inflows in the US. Understanding the factors associated with capital flows helps policy makers to predict future capital flows and analyse the international implications of domestic macroeconomic policy. Yet the theoretical relationship between net capital inflows and relative economic conditions is ambiguous. Using quarterly data from 1988 to 2003, we analyse the relation between a set of relative macroeconomic variables and net … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…These portfolio trends are consistent with historical US Treasury data. For example, Simpson, Tomljanovich, and Georgiev (2005) report that Western Europe, Canada, Japan, and Australia were sources of more than 64% of US‐bound portfolio flows during the period 1988‐2003. Our data are broadly consistent with these trends.…”
Section: Sample Construction and Characteristicsmentioning
confidence: 99%
“…These portfolio trends are consistent with historical US Treasury data. For example, Simpson, Tomljanovich, and Georgiev (2005) report that Western Europe, Canada, Japan, and Australia were sources of more than 64% of US‐bound portfolio flows during the period 1988‐2003. Our data are broadly consistent with these trends.…”
Section: Sample Construction and Characteristicsmentioning
confidence: 99%
“…For the second motivation of capital flow, if foreign investors benefit from higher returns in the host country's capital market, this benefit can translate in to a lower cost of capital for the recipient country. Past research showed that macroeconomic fundamentals mattered in determining stock return indexes and their volatility (Elhossiny 2005;Simpson, Tomljanovich et al 2005). Moreover, both economic and political stabilities were important determinant of a country's creditworthiness and credit rating, which in turn affected the country's access to international portfolio capital and the cost of capital.…”
Section: Introduction and Rationalementioning
confidence: 99%